Jezikovno in medkulturno izobraževanje na razredni stopnji osnovne šole - Mithans, Monika; Brumen, Mihaela (Revija za elementarno izobraževanje, 2011)
Raising language awareness and intercultural competence in primary school. The paper presents language awareness and intercultural competence at the primary level. They are both highly important topics, especially in professional circles. The first part introduces theoretical issues of foreign language learning and inter- cultural understanding at the primary level. The second part presents the results of the study; its purpose was to determine language awareness and intercultural competence of primary level learners and to determine the differences between age groups. The results of this study show that young learners at the primary level are interested in foreign languages and they show positive feelings about other cultures and their members, however, insufficient knowledge in foreign languages and culture are the main obstacles for their lack of communication and socializing with other cultures. This could be avoided by introducing an effective language policy and intercultural contents in the lower classes of primary schools. This would allow future generations to peacefully coexist in a multicultural society.